2021
DOI: 10.15407/biotech14.01.81
|View full text |Cite
|
Sign up to set email alerts
|

FORMATION OF THE EUBACTERIAL COMPLEX IN THE RHYOSPHERE OF SUGAR BEET (Beta vulgaris) UNDER DIFFERENT FERTILIZATION SYSTEMS

Abstract: The aim of the work was to determine the quantitative, qualitative composition and taxonomic structure of the eubacterial complex in the rhizosphere of sugar beet under different fertilizer systems. Microbiological methods were used to determine the content of microorganisms in the rhizosphere of sugar beet. Molecular methods were used to determine taxonomic structure as well as metagenome of the eubacterial complex of microorganisms. In the agrocenosis of sugar beet under different fertilizer systems the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…These observations generally support our results, especially regarding elevation, as mean elevation was significantly higher ( p < 0.0001) for pine stands than for hardwood stands (20.0 ± 0.5 vs. 10.4 ± 1.4 m, respectively). Finally, Hudz and Skivka (2021) found members of the Syntrophobacteraceae to be highly sensitive to soil fertility, as they appear to be for our sites.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…These observations generally support our results, especially regarding elevation, as mean elevation was significantly higher ( p < 0.0001) for pine stands than for hardwood stands (20.0 ± 0.5 vs. 10.4 ± 1.4 m, respectively). Finally, Hudz and Skivka (2021) found members of the Syntrophobacteraceae to be highly sensitive to soil fertility, as they appear to be for our sites.…”
Section: Resultssupporting
confidence: 55%
“…Finally, Hudz and Skivka (2021) found members of the Syntrophobacteraceae to be highly sensitive to soil fertility, as they appear to be for our sites.…”
Section: Soil Microbiomesupporting
confidence: 66%
“…Regarding the rhizosphere of sugar beet, microbial community analyses with recent molecular biological technologies have targeted rhizosphere soil (Mendes et al, 2011;Zachow et al, 2014;Hudz and Skivka, 2021) and the taproot (Shi et al, 2014;Tsurumaru et al, 2015), but not the lateral roots, except in our study described above (Okazaki et al, 2021). A microbial community analysis using an automated ribosomal intergenic spacer previously demonstrated that plant growth stages influenced the diversity of the rhizosphere microbial community in tuber peelings of sugar beet (Houlden et al, 2008).…”
mentioning
confidence: 88%
“…Although sugar beet is one of the major crops in temperate regions, only a few studies have conducted a bacterial community analysis of its phytosphere. By using Phylo-Chip, Mendes et al (2011) reported that Proteobacteria was the most dominant phylum followed by Firmicutes, Actinobacteria, and Bacteroidetes in the rhizosphere soil of sugar beet seedlings grown in arable soil, while Hudz and Skivka (2021) showed that the rhizosphere soil bacteria of sugar beet were exclusively dominated by Proteobacteria and Actinobacteria. Shi et al (2014) demonstrated that the endophytic bacteria of the taproot were exclusively dominated by Proteobacteria, particularly Alphaproteobacteria, throughout the entire growth stages of sugar beet.…”
Section: Overview Of Taxonomic Features Of Lateral Root-associated Ba...mentioning
confidence: 99%
“…Results showed that most plant-beneficial bacteria detected on various plant-based media could not be detected by metabarcoding. The microbiome of the sugar beet has previously been analyzed using metabarcoding from various aspects: seasonal shifts in the lateral root microbiome [ 6 ], spatiotemporal changes in endophytic bacterial diversity [ 34 ], the rhizobiome of the sugar beet under different fertilizer systems [ 35 ], the leaf bacteriome in relation to the susceptibility of the sugar beet to beet curly top virus [ 36 ], and Cercospora leaf spot disease [ 37 ]. In this study, the microbiome of the sugar beet was investigated in two plant parts, the root and the leaf, and compared in different plant development stages (May, July, and October).…”
Section: Discussionmentioning
confidence: 99%